Tight-binding description of graphene - Maultzsch, Janina; et al. (Physical Review B, 2002)
We investigate the tight-binding approximation for the dispersion of the pi and pi* electronic bands in graphene and carbon nanotubes. The nearest-neighbor tight-binding approximation with a fixed gamma(0) applies only to a very limited range of wave vectors. We derive an analytic expression for the tight-binding dispersion including up to third-nearest neighbors. Interaction with more distant neighbors qualitatively improves the tight-binding picture, as we show for graphene and three selected carbon nanotubes.